Clinical topics in disorders of intellectual development - Woodbury-Smith, Marc (London : RCPsych Publications, 2015)
This comprehensive work addresses the care and treatment of adults and children who have disorders of intellectual development (also known as intellectual or learning disabilities). It focuses specifically on the interface between intellectual disabilities and genetics, ageing, epilepsy and forensic psychiatry. A whole section is devoted to the diagnosis, assessment and treatment of autism spectrum disorders. Other topics include: comorbid mental health problems; behavioural problems; psychopharmacology; and service provision. There are references to the up-to-date evidence-based literature throughout the text which aims to inform clinical practice. Written by eminent clinicians and experts in their field, the majority of chapters were specially commissioned for this book, whilst a few have previously appeared in the journal Advances in Psychiatric Treatment (now known as BJPsych Advances) and have now been fully updated.
Title from publisher's bibliographic system (viewed on 19 Jan 2018).
Keywords: People with mental disabilities